Impact of hereditary angioedema attacks on health-related quality of life and work productivity - Maeve O'Connor, MD; Paula J. Busse, MD; Timothy J. Craig, DO; Cristine Radojicic, MD; H. James Wedner, MD; Sherry Danese, MBA, BS; Julie Ulloa, BS; Vibha Desai, PhD; Tomas Andriotti, PhD, MPH; Paul K. Audhya, MD, MBA; Sandra Christiansen, MD (World Allergy Organization Journal, 2025)
Background: Hereditary angioedema (HAE) negatively impacts health-related quality of life (HRQoL). Few studies have characterized impairments to HRQoL, work productivity, and well-being during and following HAE attacks. Methods: Patients with ≥1 HAE attack in the previous 3 months were recruited by the United States (US) HAE Association (HAEA) to complete an online survey. Respondents were categorized into those who did (Treated Cohort) and did not (Untreated Cohort) manage their last attack with on-demand treatment (OD). Adapted versions of the EuroQol–Five Dimensions–Five Levels (EQ-5D-5L), EuroQol Visual Analogue Scale (EQ VAS), and Work Productivity and Activity Impairment–General Health assessments were used. Results: Attacks negatively impacted HRQoL and social and physical aspects of well-being in the Treated (N = 94) and Untreated (N = 20) Cohorts. In the Treated Cohort, mean EQ-5D-5L index score was 0.849 “Today” and 0.568 “During the last treated attack,” with the latter score indicating substantial impairment in HRQoL. Mean EQ-5D-5L index scores trended lower as time to OD increased, with mean scores of 0.667 for those treating <1 h and 0.593-0.504 for those treating ≥1 to <8 h from attack onset. The percentage of patients with mild attacks decreased as time to OD increased (from 50% for those treating <1 h to 17–33% for those treating ≥1 h from attack onset), and mean EQ-5D-5L index scores decreased as attack severity increased (mild, 0.742; severe, 0.444). Generally, mean EQ VAS scores decreased as time to OD increased, from 60.1 in those treating <1 h to 53.3 in those treating ≥8 h from attack onset. In the week following attack onset, average levels of absenteeism, presenteeism, and overall work impairment were 15%, 35%, and 39%, respectively. Despite attacks being of milder severity, declines in HRQoL (mean EQ-5D-5L and EQ VAS scores “During the last attack”: 0.661 and 73.0, respectively) and impairments in work productivity (mean level of absenteeism, presenteeism, and overall work impairment: 12%, 32%, and 36%, respectively) were also observed in the Untreated Cohort. Conclusions: Late-treated and untreated attacks were associated with reduced HRQoL and work productivity, driven by attack severity. The negative impact of attacks may be reduced by increasing compliance with HAE guidelines (ie, consider OD for all attacks and treat as soon as possible), and by addressing barriers to OD in general and early treatment in particular.